PERTANGGUNGJAWABAN PIDANA TERHADAP ORANGTUA YANG TIDAK MELAPORKAN ANAKNYA SEBAGAI PECANDU NARKOTIKA BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Hafiz Akbar Ritonga; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The number of children who become victims of narcotics higher each year, required an effective way in order to reduce the number of children who become drug addicts getting down. To the authors need to raise the issue of children who become addicted to narcotics, to be a deterrent effect for the cause of children becoming drug addicts, and to be also held prtanggungjawabannya. The purpose of this thesis, namely: First, the need for criminal responsibility by parents to their children who become addicted to narcotics, second, the need to excuse criminal eraser against liability legislation of conflicting namely Law On Narcotics with the Child Protection Act. This type of research can be classified into types of normative legal research that discusses the general principles of law, systematic law and comparative law. From the research there are problems, there are two main things that Dapa concluded. First, So if I researched, the person most responsible for actually increasing the number of children who became a drug addict is a parent. In accordance with Act No. 35 of 2014, the parent is obliged to protect the mental and physical development of the child. And if the author raised through the theory of criminal liability, the parent is the person most responsible. Thus, according to the author of the number of children who become drug addicts rehabilitated and imprisoned should be accompanied by parents who participate become criminal offenders because they have neglected to keep her child. In accordance with Article 55 Paragraph (1) of Law No. 35 of 2009, parents have been deemed to know even though he did not know if his son became a drug addict, and if it does not do notifiable be subject to criminal sanctions in accordance with Article 128 of Law No. 35 of 2009. Second, the author also analyzes the juridical what if the parents have their own initiative to undertake rehabilitation treatment in private by not required to report to the authorities in accordance with Law No. 35 of 2009. On one side of the parents run the obligation to carry out rehabilitation treatment to children with do not notifiable due to negative stigma society and can be a delay in the child's education according to the Law on the Protection of Children. Keywords: Narcotics Addiction - Criminal Liability - Sanction - Liability Parents